Monitoramento vetorial e do vírus dengue, Belo Horizonte, Minas Gerais. - Jeronimo Sergio Avendanha (2006)
Dengue Virus, agent of dengue fever, depends on the vector Aedes aegypti to complete his classical cycle, man vector man. Dengue epidemics are associated with high rates of infestation by the vector, whose control is the main way of prevention. The aim of the present study was monitoring the vector and the virus through the number of Aedes aegypti eggs collected as an auxiliary in the fight against the mosquito, control and prevention of Dengue epidemics. In Pampulha, the area that was monitored, 205 ovitraps were installed and, in the period from the 28th week of 2001 to the 27th week of 2005, were inspected weekly for maintenance, egg collection counting and specification. The three indexes obtained: (OPI) ovitrap positivity; (EDI) egg density and (VDI) vectorial density were associated to Dengue fever notifications and analyzed in graphics by time series, fact that enabled the identification of the levels of vector infestation connected to the favoring of viral circulation. The values for the indexes chosen to indicate the limit between risk and control situations were 40 for IDV and 60 for IPO and IDO. The viral monitoring, through the search of infected larva, did not detect any viral circulation in the vector samples, a result that is consistent with the low level of Dengue fever cases confirmed in that period. The association observed between the levels of vector infestation and viral circulation point out that vectorial monitoring by the use of ovitraps is an important tool in dengue surveillance for its ability to indicate risk of epidemics. The continuous follow-up of the levels of vectorial infestation and the possibility of monitoring viral circulation through the search of virus in the larva obtained from the eggs collected justify the set up and maintenance of this kind of procedure.